Association of cardiac and vascular changes with ambient PM2.5 in diabetic individuals - Buse John B; Schmitt Mike T; Herbst Margaret C; Cascio Wayne E; Graff Don W; Neas Lucas M; Schneider Alexandra; Peters Annette; Devlin Robert B (Particle and Fibre Toxicology, 2010)
Abstract Background and Objective Exposure to fine airborne particles (PM2.5) has been shown to be responsible for cardiovascular and hematological effects, especially in older people with cardiovascular disease. Some epidemiological studies suggest that individuals with diabetes may be a particularly susceptible population. This study examined effects of short-term exposures to ambient PM2.5 on markers of systemic inflammation, coagulation, autonomic control of heart rate, and repolarization in 22 adults (mean age: 61 years) with type 2 diabetes. Methods Each individual was studied for four consecutive days with daily assessments of plasma levels of blood markers. Cardiac rhythm and electrocardiographic parameters were examined at rest and with 24-hour ambulatory ECG monitors. PM2.5 and meteorological data were measured daily on the rooftop of the patient exam site. Data were analyzed with models adjusting for season, weekday, meteorology, and a random intercept. To identify susceptible subgroups, effect modification was analyzed by clinical characteristics associated with insulin resistance as well as with oxidative stress and by medication intake. Results Interleukin (IL)-6 and tumor necrosis factor alpha showed a significant increase with a lag of two days (percent change of mean level: 20.2% with 95%-confidence interval [6.4; 34.1] and 13.1% [1.9; 24.4], respectively) in association with an increase of 10 μg/m3 in PM2.5. Obese participants as well as individuals with elevated glycosylated hemoglobin, lower adiponectin, higher ferritin or with glutathione S-transferase M1 null genotype showed higher IL-6 effects. Changes in repolarization were found immediately as well as up to four days after exposure in individuals without treatment with a beta-adrenergic receptor blocker. Conclusions Exposure to elevated levels of PM2.5 alters ventricular repolarization and thus may increase myocardial vulnerability to arrhythmias. Exposure to PM2.5 also increases systemic inflammation. Characteristics associated with insulin resistance or with oxidative stress were shown to enhance the association.